2014
DOI: 10.17221/548/2014-pse
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate fertilizer value of heat treated sewage sludge ash

Abstract: This study focuses on the question whether heat treated sewage sludge ashes are more favourable as fertilizers than untreated sewage sludge ashes (USSA) and whether their fertilization effects are comparable with commercial triple superphosphate (TSP). In a pot experiment, maize was fertilized either with one of three heat treated and Na-, Ca- and Si-compounds amended sewage sludge ashes (two glown phosphates, steel mill slag + sewage sludge ash) or USSA or TSP as control. Fertilization with USSA did not incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 6 publications
(7 reference statements)
9
37
1
2
Order By: Relevance
“…This result was in line with earlier work, showing that phosphorus in sewage sludge ash is generally not readily taken up by plants [9]. On the other hand, there may be considerable variations between different sewage sludge ashes, depending on the processing of sewage sludge in the water treatment plant [7].…”
Section: Do the Different Recycled Fertiliser Products Tested Have Posupporting
confidence: 91%
See 2 more Smart Citations
“…This result was in line with earlier work, showing that phosphorus in sewage sludge ash is generally not readily taken up by plants [9]. On the other hand, there may be considerable variations between different sewage sludge ashes, depending on the processing of sewage sludge in the water treatment plant [7].…”
Section: Do the Different Recycled Fertiliser Products Tested Have Posupporting
confidence: 91%
“…This was probably related to an increase in soil pH from ~5.6 in the TSP treatment to ~6.5 in the LDS/SSA treatment (Additional file 1: Table S1), since the availability of phosphates in soil is generally highest close to neutrality [59]. Severin et al [9] found that the LDS/SSA product had high efficiency as a P fertiliser [9] in accordance with this study's results, yielding a P-fertilisation effect comparable to TSP. This shows the potential of this technology to produce a highly effective P fertiliser, partly based on sewage sludge devoid of any organic contaminants.…”
Section: Do the Different Recycled Fertiliser Products Tested Have Pomentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with the data on water extractable P in the sludges where the level in the Danish sludge was three times higher than in the German sludge (Table 4). Furthermore, the availability of P in sewage sludge ashes can be quite different depending on the processing of the sludge in the water treatment plant [47].The very high fertilizer efficiency recorded for the P-enriched BOF slag has been observed earlier in wheat [45] and maize [42].…”
Section: Variable P Fertilizer Effects (P Be0)mentioning
confidence: 99%
“…The TSP (20% P) was provided by Landor in Switzerland and RP (12% P) by Herbert Molitor in Germany. The additional P treatments consisted of recycled inorganic fertilizers (sewage sludge ashes and P-enriched BOF (basic oxygen furnace) slags [42]) and organic fertilizers (fresh biogas digestate, mature compost from green wastes, composted cow and horse manures, and sewage sludge). They were characterized by the local laboratories (Table 4) for their dry matter content, total P content, water extractable P, total potassium (K) and N content, and their ammonium N content.…”
Section: P Fertilization Treatmentsmentioning
confidence: 99%